Vermiculite-based energy-saving concretes: experimental study of strength (Международный научный журнал «Инженер», 2026)
This study investigates the effect of vermiculite from the Tebinbulak deposit on the strength characteristics of concrete. Bending and compression tests were conducted on samples with varying vermiculite content. It was established that increasing the proportion of vermiculite reduces concrete strength but can contribute to improving its thermal insulation properties. The obtained results may be useful for developing lightweight and energy-efficient concrete composites.